The Quality of The Translation by Instragam Account Abu Azzam (@abuazzamtv) of The Arabic Clips to Indonesian - Ferdian, Fadhil (Al-Muyassar: Journal of Arabic Education, 2024)
The videos published on Instagram have a significant impact on changing society in this era. The current communication channels can influence society, especially Muslims, towards either good or evil, depending on what they see on these social media platforms. If the translation is accurate and understood by the viewers, where it suits the target language without distorting its meaning from the source language, using translation in video clips makes it easier for viewers to understand the intended message in Arabic videos. However, sometimes reading the translation does not enhance understanding but rather confuses the viewers, making it difficult for them to grasp the meaning. One contributing factor is that the translator faithfully presents the source text message, but viewers find it challenging to comprehend the translation. The objectives of this research are as follows: 1) To determine the method used by Abu Azam for translation. 2)To assess the quality of Abu Azam's Instagram account in translating Arabic lesson clips into Indonesian. The research methodology employed is qualitative, using content analysis. The findings indicate the following: 1) Out of 7 video clips, 4 utilize literal translation, 2 employ communicative translation, and 1 uses free translation. 2) In terms of translation accuracy among the 7 video clips, the researcher found that 6 video clips effectively convey the messages, while 1 video clip has some shortcomings in conveying the messages. Regarding acceptability, 4 video clips received a satisfactory rating, 2 received an unsatisfactory rating, and 1 video clip received an unacceptable rating. In terms of comprehension, all 7 video clips were highly understandable, with the viewers easily comprehending the translations.